Mastering Cranial Nerve Anatomy: A Schematic Approach - Samuel Paskin-Flerlage; Lee Eisner (Association of American Medical Colleges, 2015)
Abstract Introduction The physical constraints of the skull and complex spatial relationships of the anatomy pose unique challenges to the study of head and neck and contribute to its notoriety amongst students. Mastering the cranial nerves is a tedious but imperative learning task; the complicated pathways to target tissues and intricate relationships each one and its bony confine. This module aims to assist medical, dental, and allied health students in their study of cranial nerve anatomy by providing a unique anatomical reference that presents the key structures/relationships of the cranial nerves in relation to physiological functions and pathophysiological implications. Methods This resource can be used either for self-directed learning or a didactic setting, during which it may serve as an aid in the initial presentation, or material review to reinforce key concepts. We encourage users to review each slide sequentially, a process that may require 60 minutes to allow for a thorough and meaningful lesson. Results This module was formally incorporated into the State University of New York Downstate Medical Center College of Medicine curriculum in 2014, where it served as a supplemental learning activity during gross anatomy of the head and neck region. A class survey of 62 users, surveyed using a 10-point scale reported (on average) a utility of 8.7, an improvement in relative knowledge of cranial nerve anatomy and function from 3.8 (prior to use) to 8.2 (after use), and a strong belief that the schematics contained within the module provided a unique perspective not found in other resources such as textbooks and atlases (8.2). Discussion This resource provides a unique prospective on cranial nerve anatomy, meeting the educational needs of the visuospatial learner by filling a necessary void in the current educational resources. This module challenges students to apply fundamental anatomical and functional knowledge to clinical scenarios.